2000
DOI: 10.1016/s0194-59980070020-9
|View full text |Cite
|
Sign up to set email alerts
|

Complications after Total Laryngectomy in Nonradiated Laryngeal and Hypopharyngeal Carcinomas

Abstract: To study the complications of total laryngectomy, we evaluated 471 previously untreated patients who underwent total laryngectomy between 1980 and 1997. This series consisted of 358 patients with primary carcinoma of the larynx and 113 with carcinoma of the hypopharynx. Concurrent neck dissection was performed in 85% of patients. Complications were studied in relation to age, T and N stage, previous tracheostomy, neck dissection, margins, reconstruction, tracheoesophageal puncture, and surgeon. Complication tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 17 publications
3
4
0
Order By: Relevance
“…The incidence of PCF as well as its rates in the primary and salvage setting are inconsistently reported in the literature. After primary TL, the rate of PCF was found to range between 8 and 25% [ 1 , 4 , 9 , 10 , 11 , 12 ], and the incidence of 20.8%, after primary TL, in our series is within the expected range. Similarly, the reported incidence of PCF after salvage TL was between 20 and 40% [ 1 , 4 , 11 , 13 , 14 ], but a wider range of 14–57% was additionally stated [ 12 ].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The incidence of PCF as well as its rates in the primary and salvage setting are inconsistently reported in the literature. After primary TL, the rate of PCF was found to range between 8 and 25% [ 1 , 4 , 9 , 10 , 11 , 12 ], and the incidence of 20.8%, after primary TL, in our series is within the expected range. Similarly, the reported incidence of PCF after salvage TL was between 20 and 40% [ 1 , 4 , 11 , 13 , 14 ], but a wider range of 14–57% was additionally stated [ 12 ].…”
Section: Discussionsupporting
confidence: 66%
“…In the literature, not only are a wide range of PCF incidence rates reported, from 0% [ 7 ] to 80% [ 8 ], but also a variety of potential risk factors. In general, the incidence of PCF particularly depends on the type of TL: after primary TL, the incidence is between 8 and 25% [ 1 , 4 , 9 , 10 , 11 , 12 ], and after salvage TL, it is considerably higher, reaching 14–57% [ 1 , 4 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Herranz et al evaluated complications of TL in 471 patients with primary laryngectomy and found no association between PreOT and laryngectomy complications. 13 Basheeth et al investigated predictors of pharyngocutaneous fistula after TL in 74 patients and found that PreOT was not a significant predictor of fistula formation. 5 Similarly, we identified no difference in rates of surgical or medical complications in patients receiving a PreOT or not in either laryngectomy group.…”
Section: Discussionmentioning
confidence: 99%
“…8,[10][11][12] Yet, these findings are disputed, and there is a lack of comprehensive data on the effect of PreOT timing on complications after TL. 13,14 The primary objective of this study is to assess whether PreOT increases risk of complications after TL and to determine if timing of tracheostomy creation is associated with an increased risk. Here we study whether PreOT within 14 days of TL is associated with complication rates after subsequent TL.…”
mentioning
confidence: 99%
See 1 more Smart Citation